Effects of beak-treatment styles on beak morphology and production performance of layer chicks aged 0–8 weeks - Duan, Lin; Zhao, Xiao-Yu; Hao, Er-Ying; Wang, Chuan-Wen; Wang, De-He; Chen, Hui; Wang, Zhong-Qiang; Xu, Li-Jun; Di, Ke-Qian (Frontiers in Veterinary Science, 2025)
IntroductionDouble-infrared (IR-D) and laser energy sources (LAS) are two types of newly beak treatment equipment. Although the IR-D and LAS techniques have been developed by changing the number and type of energy sources, their effects on layer chicks are yet to be systematically studied.MethodsIn this study, we placed 4,416 layer chicks into groups subjected to single-infrared energy sources (IR-S), IR-D, and LAS beak treatment on hatching day and a sham untreated control (CON) group; the beak sloughing, growth and histomorphology, body weight (BW), feed intake (FI), and other performance indicators were measured.ResultsResults showed that the beak length at 4 to 8wk in LAS group was significantly higher than that in IR-S and IR-D groups (p < 0.05), and showed a better symmetry. The beak bone mineral density (BMD) and the beak bone mineral content (BMC) at 3–4 weeks was the lowest in the CON group. The BW at 1–4 weeks and the FI at 1 and 3 weeks in the CON group were significantly higher than those in the IR-S and IR-D groups (p < 0.05), whereas there was no significant difference between the BW and FI of the CON and LAS groups from 1 to 8 weeks. The liver weight percentage from 1 to 2 weeks and the bursa Fabricius weight percentage at week 8 in the CON group were significantly higher than those in the experimental groups (p < 0.05).DiscussionThis study concluded that the LAS group had certain advantages in beak length, symmetry, BW, and FI and provided a reference for evaluating the effects of beak treatment methods on layer chicks.